A short peptide with selective anti-biofilm activity against Pseudomonas aeruginosa and Klebsiella pneumoniae carbapenemase-producing bacteria. (October 2019) - Cardoso, Marlon H.; Santos, Viviane P.M.; Costa, Bruna O.; Buccini, Danieli F.; Rezende, Samilla B.; Porto, William F.; Santos, Matheus J.; Silva, Osmar N.; Ribeiro, Suzana M.; Franco, Octávio L.
Abstract: Biofilm-related infections represent an enormous clinical challenge nowadays. In this context, diverse studies are underway to develop effective antimicrobial agents targeting bacterial biofilms. Here, we describe the antibacterial and anti-biofilm activities of a short, cationic peptide named R5F5, obtained from sliding-window analysis based on a peptide (PcDBS1R5) derived from Plasmodium chabaudi . Ten fragments were generated (R5F1 to F10) and submitted to initial antibacterial assays against Pseudomonas aeruginosa . As a result, R5F5 showed the highest antimicrobial activity. We therefore carried out further antibacterial and anti-biofilm assays against P. aeruginosa and Klebsiella pneumonia e carbapenemase-producing bacterial strains. R5F5 revealed selective anti-biofilm activity, as the peptide inhibited >60% biofilm formation in all cases from 8 to 64 μg·mL −1 . Moreover, R5F5 was not hemolytic against mice erythrocytes at 640 μg mL −1 . Cytotoxic effects on human lung fibroblast cells were not detected at 160 μg·mL −1 . Structural studies revealed that R5F5 presents random coil conformations in water and 50% 2, 2, 2-trifluoroethanol (TFE)/water (v/v), whereas amphipathic, extended conformations were observed in contact with sodium dodecyl sulfate (SDS) micelles. Thus, here we report a novel peptide with selective anti-biofilm activity against susceptible and resistant bacterial strains, with no toxicity toward mammalian cells and that adopts a stable structure in anionic environment. Graphical abstract: Image 1 Highlights: R5F5 is the most active sliding-window fragment from PcDBS1R5. R5F5 presents selective antibiofilm activity Gram-negative bacteria. The fragment R5F5 is non-toxic toward mammalian cells (dose-dependent). In the presence of SDS micelles R5F5 adopts a stable, amphipathic arrangement.